Impact of Long-Term Atrazine Use on Groundwater Safety in Jilin Province, China - Yue GENG; Jing MA; Ran JIA; Li-qin XUE; Chuan-jiang TAO; Chong-jiu LI; Xiao-dong MA; Yan LIN (Journal of Integrative Agriculture, 2013)
The long-lasting application of representative herbicide atrazine (ATR) has given rise to the accumulation of its residues in the groundwater. To investigate the impact of long-term ATR use on groundwater safety, the residues of ATR and its metabolites, desethylatrazine (DEA), deisopropylatrazine (DIA) and hydroxyatrazine (HA) were monitored in groundwater and top soil at the major corn growing region of Qian'an and Gongzhuling in Jilin Province, China. The residues of the target compounds were analyzed by UPLC-MS/MS. The limits of detection (LODs) of ATR, DEA, DIA, and HA were 0.5, 0.5, 5, and 0.5 ng L−1 in groundwater and 0.33, 0.33, 3.3, and 0.33 μg kg−1 in soil. The target compounds were found in 94% of groundwater samples and 100% of soil samples. The compounds detected most frequently in groundwater were ATR (89%), DEA (64%) and HA (17%), whereas in soil were ATR (97%), DEA (36%) and HA (97%). DIA was not detected in any determined groundwater and soil sample. Average residues were 106.8 ng L−1 for ATR, 0.9 ng L−1 for DEA and 0.3 ng L−1 for HA in groundwater, whereas 11.1 μg kg−1 for ATR, 0.4 μg kg−1 for DEA and 7.8 μg kg−1 for HA in soil. ATR residues detected in groundwater samples were below standards for drinking water quality (GB5749-2006, 2 μg L−1), while the total residues of ATR and its chloro-s-triazine metabolites (DEA and DIA) were below current WHO (World Health Organization) guideline value (GV, 0.1 mg L−1). In addition, concentrations of HA in groundwater were determined below current WHO GV (0.2 mg L−1). The results indicated that ATR is safe to be used in Jilin Province under the current application scheme. However, total residues of ATR and DEA were detected in nearly all wells, thus, it is necessary to pay attention on groundwater monitoring for ATR and its metabolites.